Use of indecent words in a public place as a misdemeanour (Ius Novum, 2019)
An offence involving in the use of indecent words in a public place is one of the acts classified in Chapter XVI Misdemeanour Code that violates public decency. Its subject matter consists in placing an obscene announcement, inscription or drawing or using obscene words in a public place. Both the notion of public morality and the sign of indecency are indeterminate in nature. Similarly, the concept of an “obscene word” is not very precise. Both public morality and obscenity are highly relative, perceived differently by different social groups and considered more or less acceptable depending on the age of the audience. The pursuit of offences involving the use of indecent words cannot, however, be selective. One should distinguish between the use of vulgar words as an insult and a specific “interlude”.
Keywords: misdemeanour; public decency; indecent words; pornography; profanity